Antibody‐independent targeted quantification of TMPRSS2‐ERG fusion protein products in prostate cancer. Issue 7 (21st February 2014) - He, Jintang; Sun, Xuefei; Shi, Tujin; Schepmoes, Athena A.; Fillmore, Thomas L.; Petyuk, Vladislav A.; Xie, Fang; Zhao, Rui; Gritsenko, Marina A.; Yang, Feng; Kitabayashi, Naoki; Chae, Sung-Suk; et al.
Abstract : Fusions between the transmembrane protease serine 2 (TMPRSS2) and ETS related gene (ERG) represent one of the most specific biomarkers that define a distinct molecular subtype of prostate cancer. Studies of TMPRSS2‐ERG gene fusions have seldom been performed at the protein level, primarily due to the lack of high‐quality antibodies suitable for quantitative studies. Herein, we applied a recently developed PRISM (high‐pressure high‐resolution separations with intelligent selection and multiplexing)‐SRM (selected reaction monitoring) strategy for quantifying ERG protein in prostate cancer cell lines and tumors. The highly sensitive PRISM‐SRM assays provided confident detection of 6 unique ERG peptides in both TMPRSS2‐ERG positive cell lines and tissues, but not in cell lines or tissues lacking the TMPRSS2‐ERG rearrangement, clearly indicating that ERG protein expression is significantly increased in the presence of the TMPRSS2‐ERG gene fusion. Significantly, our results provide evidence that two distinct ERG protein isoforms are simultaneously expressed in TMPRSS2‐ERG positive samples as evidenced by the concomitant detection of two mutually exclusive peptides in two patient tumors and in the VCaP prostate cancer cell line. Three peptides, shared across almost all fusion protein products, were determined to be the most abundant peptides, providing "signature" peptides for detection of ERG over‐expression resulting from TMPRSS2‐ERG gene fusion. The PRISM‐SRM assays provide valuable tools for studying TMPRSS2‐ERG gene fusion protein products in prostate cancer. Highlights: PRISM‐SRM enabled highly sensitive detection of TMPRSS2‐ERG fusion protein products. ERG protein expression is highly correlated with TMPRSS2‐ERG gene rearrangements. At least two groups of ERG protein isoforms were simultaneously expressed. Three signature peptides for detection of ERG expression were identified.